Strategi Kepemimpinan Sekolah dalam Peningkatan Mutu Pendidikan (Studi Multi Kasus pada SMA Islam Al-Azhar BSD Tangerang Selatan Dan SMA Islam Al-Azhar BSD Cilengsi) - Rahmat Rizky Basuki; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
This research aims to analyze school leadership strategies in improving the quality of education at Al-Azhar Islamic High School BSD South Tangerang and Al-Azhar Islamic High School Cileungsi. Using a qualitative approach and multi-case study method, this research identifies the strategic steps of school principals in improving the quality of education. The research results show that transformational and collaborative leadership play an important role in the success of improving the quality of education. The strategies implemented include developing teacher competency, using technology in learning, and strengthening school culture. This study provides practical insights for educational leaders in managing schools effectively.